Endoscopic urgency triaging impacts acute variceal bleeding patient survival and hospital stay length - Amr Shaaban Hanafy; Ahmed Behiry; Dalia Mahmoud Abdelmonem Elsherbini; Hasnaa Ali Ebrahim; Ateya Megahed Ibrahim; Khalid I. AlQumaizi; Moaz Abulfaraj; Mohamed El-Sherbiny; Hany A. Elkattawy (Libyan Journal of Medicine)
Upper gastrointestinal bleeding (UGIB) needs accurate endoscopic timing. This study investigates the debate on the necessity of upper endoscopy in UGIB, proposes predictors for adverse outcomes if urgent endoscopy is deferred, and assesses the risk to patient health or results compared to non-urgent endoscopy. A non-randomized controlled study conducted at a single center involved 200 patients with acute life-threatening UGIB. The study group comprised 100 who had an urgent endoscopy within 6 h and a control group included 100 who waited or declined the procedure within 6–24 h. Glasgow-Blatchford score was used for risk stratification of UGIB. Doppler ultrasound was applied to measure lower esophageal wall thickness. D-dimer, lactate, and procalcitonin were measured. The study group revealed recurrent bleeding after 13.5 ± 3.6 days. Death occurred in 4 (4%) which is statistically significant lower (p = 0.024) compared to the control group due to hypovolemic shock, pulmonary embolization, or aspiration pneumonia. Control group showed recurrent bleeding following 15.8 ± 4.7 days (p = 0.306). Death occurred in 14 (14%) of patients due to hypovolemic shock, disseminated intravascular coagulation, or pulmonary embolization. A shorter hospital stay (8.4 ± 3.2 days) was evident in the study group compared to the control group (16.4 ± 2.76 days, p < 0.001). D-dimer, serum lactate, and procalcitonin (Adjusted Odds Ratio (AOR) = 1.004, 2.207, 0.563, p < 0.001, <0.001, 0.011, respectively), and their corresponding values at follow-up (AOR = 0.988, 0.528, 177.04, p < 0.001, 0.011, <0.001, respectively) were significantly associated with higher mortality. Waiting time till endoscopy, baseline D-dimer (AOR = 1.794, 0.998, p < 0.001, 0.014, respectively), creatinine, procalcitonin, and esophageal wall thickness at follow-up were significantly associated with longer hospital stay. The study suggests that higher lower esophageal wall thickness and elevated serum lactate, D-dimer, and procalcitonin are novel triaging markers for early endoscopic intervention, which can improve patient outcomes, reduce blood transfusion risks, and eliminate unnecessary procedures.